Postoperative complications in breast reconstruction using acellular dermal matrix - V. V. Kochubey (Кубанский научный медицинский вестник)
Acellular dermal matrix (ADM) is known as an innovative material used for breast reconstruction using tissue expanders or implants. Using ADM provides additional coverage and support to the lower pole of the reconstructed breast. In the process of the present study evaluated the risk of postoperative complications when using ADM in the reconstruction based on the implant. Methods We performed a retrospective analysis of 212 consecutive immediate breast reconstruction with tissue expanders or implants, including without ADM 108 and ADM 104. Total was performed breast reconstruction in 140 patients, including 68 unilateral reconstructions and 72 bilateral reconstructions. In the group where unused ADM was higher seroma frequency 13.5% vs. 3.7%, and a higher incidence of infection 18.3% vs. 5.6%. Also, found that body mass index, a statistically significant factor for the development of seroma and infection. Conclusions ADM is a convenient material for breast reconstruction, but it is accompanied with complications such as seroma and infection. Improve the results of operations for breast reconstruction using ADM help the careful selection of patients, the choice of an adequate size of the implant and the proper postoperative management.